57.5k views
1 vote
Evaluate (2-6)^3 / -2^3 + (-4)

User Divided
by
4.4k points

1 Answer

5 votes

Solution

To evaluate


(2-6)^3\text{ / }-2^3+(-4)

We use the order of operation rule

PEDMAS

P - Parenthesis

E - Exponents

M - Multiplication

D - Division

A - Addition

S - Subtraction

Following that order; we have

Parenthesis first


\begin{gathered} (2-6)^3=(-4)^3=-64 \\ \\ +(-4)=-4 \\ \\ 2^3=8 \end{gathered}
\begin{gathered} \Rightarrow(2-6)^3\text{ / }-2^3+(-4)=-64\text{ / }-8-4 \\ \end{gathered}

Using division


-64\text{ \textbackslash -8 }=8
\Rightarrow-64\text{ / -8 -4 }=8-4=4

The answer is 4.

User Anson
by
5.5k points